Pengaruh Simulasi Kedaruratan Medik Terhadap Kompetensi Petugas Penanggulangan Bencana Daerah Provinsi Sulawesi Barat - Nursana, I Made; Ghaznawie, Mahmud; Budu, (Jurusan Keperawatan FIKES UNSOED, 2013)
Disasters almost always cause loss of property, destruction of ecosystems and causing human casualties both dead survivors in a state of emergency. The state of emergency is if not handled quickly and properly will lead to death and disability.This study aims to determine differences in the competence of emergency medical officer of the Regional. The method used is a quasi-experimental one group pretest-posttest design. Data analysis using Wilcoxon test test. There is a significant difference of knowledge, attitudes and skills of emergency medical personnel with a p value of 0.000. Significantly different attitudes emergency medical personnel before and after the simulation. Need to be implemented or simulated continuous exercise for officers to always be ready in a disaster can happen at any time.